2016
DOI: 10.1371/journal.pone.0153239
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV Status on Treatment Outcome of Tuberculosis Patients Registered at Arsi Negele Health Center, Southern Ethiopia: A Six Year Retrospective Study

Abstract: BackgroundDespite implementation of different strategies, the burden and mortality of human immunodeficiency virus (HIV)-associated tuberculosis (TB) remains a challenge in Ethiopia. The aim of this study was to assess the impact of HIV status on treatment outcome of tuberculosis patients registered at Arsi Negele Health Center, Southern Ethiopia.MethodsA six-year retrospective data (from September 2008 to August 2014) of tuberculosis patients (n = 1649) registered at the directly observed therapy short-course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
56
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 24 publications
14
56
7
1
Order By: Relevance
“…This might be due to the statistical pooling effect of the reference groups. In contrast to our study, other studies have shown an association between HIV co-infection and TB treatment outcome [27,35].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This might be due to the statistical pooling effect of the reference groups. In contrast to our study, other studies have shown an association between HIV co-infection and TB treatment outcome [27,35].…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the proportion of patients with successful treatment outcomes (cured and completed) was found to be 90.9%, which is higher than the WHO target set for the Millennium Development Goal(MDG) of 85% [31][32][33] and comparable to that of the milestone target set globally for 2025 of > 90% [1,34].Comparable findings were reported by other Ethiopian studies [5,26,[35][36][37].…”
Section: Discussionsupporting
confidence: 53%
“…TB treatment outcome is poor among HIV positive TB patients compared with HIV negative TB patients 13–17. There is a continuing need to routinely assess the likely reasons for poor treatment outcome among TB/HIV co-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Uzbekistan and Ethiopia showed the unfavorable treatment outcomes in TB with HIV patients. 24,25 The TSR among re-treatment cases was much lower than new smear positive patients. This was supported by previous studies where re-treatment cases were significantly associated with unsuccessful treatment outcome.…”
Section: Discussionmentioning
confidence: 96%